2015
DOI: 10.1038/nclimate2541
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and biotic thresholds of coral-reef shutdown

Abstract: Climate change is now the leading cause of coral-reef degradation and is altering the adaptive landscape of coral populations 1,2 . Increasing sea temperatures and declining carbonate saturation states are inhibiting short-term rates of coral calcification, carbonate precipitation and submarine cementation [3][4][5] . A critical challenge to coral-reef conservation is understanding the mechanisms by which environmental perturbations scale up to influence long-term rates of reef-framework construction and ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 47 publications
(101 reference statements)
4
91
1
Order By: Relevance
“…However, recent geological and ecological research on fossil reefs in the Great Barrier Reef (GBR) (Smithers et al, 2006, Leonard et al, 2015, Ryan et al, 2016a, 2016b and wider Indo-Pacific , Hamanaka et al, 2012, Toth et al, 2015 identified intervals of significant reef "turn-off" in response to natural environmental forces earlier in their development during the mid-to late Holocene. It is therefore important to understand the longer term histories of coral reefs as they not only provide important information about significant palaeoenvironmental change, but also provide greater insight into the persistence (or not) of reef growth through time.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…However, recent geological and ecological research on fossil reefs in the Great Barrier Reef (GBR) (Smithers et al, 2006, Leonard et al, 2015, Ryan et al, 2016a, 2016b and wider Indo-Pacific , Hamanaka et al, 2012, Toth et al, 2015 identified intervals of significant reef "turn-off" in response to natural environmental forces earlier in their development during the mid-to late Holocene. It is therefore important to understand the longer term histories of coral reefs as they not only provide important information about significant palaeoenvironmental change, but also provide greater insight into the persistence (or not) of reef growth through time.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…They were attributed to oscillating sea level and relatively cold sea-surface temperatures associated with a weakened Kuroshio Current (Hamanaka et al, 2012). In Hawaii and Panama (Toth et al, 2012(Toth et al, , 2015, cessation of reef…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been linked to increased ENSO variability (Toth et al, 2012(Toth et al, , 2015 and stronger upwelling conditions (Glynn et 15 al., 1983), favoring dissolution and erosion of reef frameworks while at the same time restricting coral growth.…”
Section: Ecological Implications For Coral Reefs 20mentioning
confidence: 99%